Endovascular treatment of head and neck arteriovenous malformations: long-term angiographic and quality of life results. (26th August 2016) - Meila, Dan; Grieb, Dominik; Greling, Bjoern; Melber, Katharina; Jacobs, Collin; Hechtner, Marlene; Schmitz, Thomas; Schlunz-Hendann, Martin; Lanfermann, Heinrich; Brassel, Friedhelm
Abstract : Aim: To present the long-term angiographic and subjective results of patients with head and neck arteriovenous malformations (HNAVMs) after endovascular treatment. Methods: We retrospectively analyzed the medical files of 14 patients with HNAVM who were treated between 2000 and 2014. The treatment of choice was a transarterial superselective microcatheter-based approach followed by embolization using liquid embolic agents. The patients were asked to answer a quality of life questionnaire about the following symptoms before and after treatment: pain, functional impairment, cosmetic deformity, impairment in daily life, and bleeding. Results: Complete or >90% closure of the AVM was achieved in 6 of 14 patients (43%). >50% shunt reduction was achieved in 10 patients (71%). Three complications were encountered in a total of 86 interventional procedures. Six patients presented with bleeding which was cured in all cases (100%). Four of the 14 patients (29%) specified pain which was resolved in two of them. Another six patients (43%) presented with functional impairment; four were cured and two noted an improvement. All 14 patients presented with cosmetic concerns; four were cured and eight experienced a clearly visible improvement. Nine of 13 patients (69%) presented with impairment in daily life which was resolved in five patients and four reported an improvement. Conclusions: Endovascular embolization is a well-tolerated therapy for HNAVM with a low complication rate. Good angiographic results, positive subjective results, and improvement in different aspects of quality of life can be achieved.